The enigmatic academy : class, bureaucracy, and religion in American education - Churchill, Christian J., 1969- (Temple University Press, 2012)
"The Enigmatic Academy is a provocative look at the purpose and practice of education in America. Authors Christian Churchill and Gerald Levy use three case studies - a liberal arts college, a boarding school, and a Job Corps centre - to illustrate how class, bureaucratic, and secular-religious dimensions of education prepare youth for participation in American foreign and domestic policy at all levels. The authors describe how schools contribute to the formation of a bureaucratic character; how middle and upper class students are trained for leadership positions in corporations, government, and the military; and how the education of lower class students often serves more powerful classes and institutions. Exploring how youth and their educators encounter the complexities of ideology and bureaucracy in school, The Enigmatic Academy deepens our understanding of the flawed redemptive relationship between education and society in the United States. Paradoxically, these three studied schools all prepare students to participate in a society whose values they oppose"--